Pearls and Pitfalls in Cardiovascular Imaging : Pseudolesions, Artifacts, and Other Difficult Diagnoses - Zimmerman, Stefan L.; Fishman, Elliot K. (Cambridge : Cambridge University Press, 2015)
Cardiovascular imagers are faced with the challenge of interpreting cases that include artifacts, unusual findings, or anatomic variants on an almost daily basis. These studies can result in confusion and may lead to misdiagnosis even for the most experienced imager. This book provides an approachable reference for practising cardiovascular imagers to aid with both commonly and uncommonly encountered entities that can result in inappropriate patient management. Through the focused use of case examples, this book reviews 100 conditions that can be seen in clinical practice, including pseudotumors, artifacts, anatomic variants, mimics, and unusual diagnoses. Each highly illustrated case follows a standard format, allowing readers to learn from real-life examples and provides an accessible and rapid source of reference for the improved interpretation of cardiovascular imaging and enhanced patient care. This text will be invaluable to radiologists, cardiologists, and trainees.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Diagnostic imaging; Diagnostic Techniques, Cardiovascular